2017
DOI: 10.1002/2017jd026510
|View full text |Cite
|
Sign up to set email alerts
|

Highly variable aerodynamic roughness length (z0) for a hummocky debris‐covered glacier

Abstract: The aerodynamic roughness length (z0) is an essential parameter in surface energy balance studies, but few literature values exist for debris‐covered glaciers. We use microtopographic and aerodynamic methods to assess the spatial variability of z0 for Lirung Glacier, Nepal. We apply structure from motion to produce digital elevation models for three nested domains: five 1 m2 plots, a 21,300 m2 surface depression, and the lower 550,000 m2 of the debris‐mantled tongue. Wind and temperature sensor towers were ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
97
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(109 citation statements)
references
References 72 publications
11
97
1
Order By: Relevance
“…The relationship between z 0 and scale is as expected for SK (cf. Miles et al, ; Quincey et al, ). Raster z 0 follows a clear trend with plot size, whereas transect z 0 shows some variation but increases overall—both demonstrate significant relationships ( r 2 > 0.9, p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The relationship between z 0 and scale is as expected for SK (cf. Miles et al, ; Quincey et al, ). Raster z 0 follows a clear trend with plot size, whereas transect z 0 shows some variation but increases overall—both demonstrate significant relationships ( r 2 > 0.9, p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…As with other similar studies, we found that using wind/temperature profiles to find z 0 is a very low‐yield approach (cf.Brock et al, ; Denby & Smeets, ; Miles et al, ; Quincey et al, ; Sicart et al, ; Smeets et al, ). Moreover, sensors had to be monitored and repaired due to harsh weather conditions meaning that instruments cannot be set up and left unattended for long periods (the wind tower at Storglaciären collapsed overnight from 12 to 13 July, hence the shortened dataset).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations